Associations of the perceived benefits and harms of COVID-19 with confidence in coping with the pandemic and mental health symptoms: a population-based survey in Hong Kong - Yao, Ying; Gong, Wei Jie; Lai, Agnes Yuen Kwan; Wu, Yongda Socrates; Sit, Shirley Man Man; Wang, Man Ping; Ho, Sai Yin; Lam, Tai Hing (Frontiers in Public Health, 2023)
Introduction Both perceived benefits and harms of COVID-19 have been reported, but whether they affect confidence in coping with the pandemic and mental health remains uncertain. Objective To examine the association of perceived benefits and harms of COVID-19 with confidence in coping with the pandemic and mental health symptoms. Methods A population-based survey was conducted on 7,535 Hong Kong adults from 22 February to 23 March 2021, when the 4th wave of COVID-19 was under control. Information on sociodemographic characteristics, perceived benefits (10 options) and harms (12 options) of COVID-19, confidence in coping with the pandemic (range 0–10), loneliness (range 0–4), anxiety (General Anxiety Disorders-2, range 0–6) and depression (Patient Health Questionnaire-2, range 0–6) was collected. Latent profile analysis was used to identify the combined patterns of perceived benefits and harms of COVID-19. The associations of combined patterns with confidence in coping with COVID-19, loneliness, anxiety, and depression were examined using linear regression (β coefficient) adjusting for sociodemographic characteristics. Results The combined patterns of perceived benefits and harms were classified into benefit (n = 4,338, 59.3%), harm (n = 995, 14.0%), and ambivalent (n = 2,202, 26.7%) groups. Compared with the ambivalent group, the benefit group had a significantly higher level of confidence (adjusted β 0.46, 95% CI 0.33 to 0.58), and lower levels of loneliness (−0.35, −0.40 to-0.29), anxiety (−0.67, 0.76 to-0.59), and depression (−0.65, −0.73 to-0.57). The harm group had a significantly lower level of confidence (−0.35, −0.53 to-0.16), and higher levels of loneliness (0.38, 0.30 to 0.45), anxiety (0.84, 0.73 to 0.96), and depression (0.95, 0.84 to 1.07). Conclusion Perceived greater benefit from COVID-19 was associated with better mental health and stronger confidence in coping with the pandemic.